2009
DOI: 10.1021/jp9096309
|View full text |Cite
|
Sign up to set email alerts
|

Role of Linear Carbon Chains in the Aggregation of Copper, Silver, and Gold Nanoparticles

Abstract: Most of the applications involving metal nanoparticles require a high resistance to aggregation and oxidation phenomena to preserve and modulate the peculiar reactivity, electronic, optical, and magnetic properties of nanoparticles. Linear carbon chains (LCCs) containing sp hybridization either as alternating triple and single bonds (polyynes) or with consecutive double bonds (cumulenes) are good candidates to create a shell that prevents such unwanted degradation phenomena. In addition, the development of rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
34
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 38 publications
1
34
0
Order By: Relevance
“…After the colloid runs dry, the 2930 cm −1 feature may originate from the precursor residue during preparing Ag colloid. Besides, the intensity of G band at 1558 cm −1 increases, due to the more effective cross-linking processes in dried Ag colloid [20]. The experimental results are the same when the excitation wavelength turns to 633 nm.…”
Section: Resultsmentioning
confidence: 63%
“…After the colloid runs dry, the 2930 cm −1 feature may originate from the precursor residue during preparing Ag colloid. Besides, the intensity of G band at 1558 cm −1 increases, due to the more effective cross-linking processes in dried Ag colloid [20]. The experimental results are the same when the excitation wavelength turns to 633 nm.…”
Section: Resultsmentioning
confidence: 63%
“…The characteristic bands of Au/polyynes/PVA film lie in the 1300-1700 cm -1 region are thought from sp 2 hybridized carbon structures [8]. Generally, the unstable polyynes reorganize towards more stable sp 2 phases by chain-chain cross-linking reactions [13].…”
Section: Resultsmentioning
confidence: 99%
“…Although mainly two Raman modes of C 2n H 2 were reported by many researchers [10][11][12][13], the positions considerably differ from each other. Hanamura et al [10] found that the SERS bands of C 8 H 2 adsorbed on Ag island film show a redshift than the Ag colloids.…”
Section: Page 2 Of 24mentioning
confidence: 90%
See 2 more Smart Citations